Head lice infestations in rural Honduras: the need for an integrated approach to control neglected tropical diseases. (13th December 2018) - Jamani, Shabana; Rodríguez, Carol; Rueda, María M.; Matamoros, Gabriela; Canales, Maritza; Bearman, Gonzalo; Stevens, Michael; Sanchez, Ana
Abstract: Background: Pediculosis capitis is a neglected tropical disease (NTD) that receives little attention in countries where it continues to be endemic. This study aimed to understand the impact of Pediculus humanus capitis infestations in the lives of Honduran children living in extreme poverty. Methods: A qualitative study on head lice infestation was conducted in June 2016 in a rural community in Honduras. Parents were invited to bring their children for head lice inspection using a dry‐combing technique with a stainless steel‐toothed comb with suction power. A semistructured questionnaire was administered to participants. Questions were broadly grouped into knowledge about transmission, control practices, barriers to treatment, and the overall impact of these infestations in children's wellbeing. Responses were coded, categorized, and organized through a theme‐based approach. Results: In total, 52 children aged 2–14 years (42 girls) and their mothers were enrolled in the study. The overall proportion of children with an infestation was 83%. Response analysis revealed a lack of understanding regarding lice transmission and stigmatization of infested children and the widespread belief that head lice were acquired during bathing in the slow‐flowing river running through the village. An agricultural plaguicide was commonly used to rid children of head lice. Conclusions: The study underscores the dire situation of the rural poor, their physical and mental health affected by pediculosis capitis as well as other NTDs. These results highlight the need to reassess approaches and action towards combating NTDS under an integrated framework.